Northwest History. Alaska. Earthquakes & Volcanoes. (1937)
quake Fairbanks Alaska Black Rapids Glacier Black Rapids Valley the Rapids roadhouse fear FEAR OF QUAKE HITS FAIRBANKS FAIRBANKS, Alaska—(U.E) — A severe earthquake in the Fairbanks district Wednesday night gave rise to fears that Black Rapids Glacier, now rushing forward at an unprecedented speed of a mile-a-month, would advance with even greater rapidity. Scientists expressed the opinion previously that an earlier quake started the 30-mile-long glacier on its movement down Black Rapids valley. The glacier is 1000 feet high and two miles wide at its face and is now within a mile of the Rapids roadhouse. The quake was one of the most severe felt in years. Buildings in Fairbanks shook and windows rattled, but no dp.mage was reported. The center of the quake was believed to be nearer the glacier, 140 miles from here, than to Fairbanks.